Evaluasi Hubungan Paralel Transformator Fakultas Teknik Universitas Riau Pada Kondisi Beban Normal Dan Beban Puncak - Niky Sudarmantoro; Firdaus Firdaus; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The development of electrical power is important issue and has more effect to development of Indonesia. One of ways to increase the amount of power needed in manufacturing parallel system for distribution transformer. This way using by Engineering Faculty, University of Riau need 475,015 kVA or approximately 59,37% from maximum limit transformer load. Load limit for distribution substation of transformer from datasheet is 400kVA p.u and for load limit from theory calculation is 381,084kVA p.u or approximately 95,271%. This losses get from loss of material transformator about 4,729%. According to standardization presented by schneider electric, USA. transformator with the least impedance will have the most current cause in short age of the transformator.Keywords : Distribution System, Parallel System, Transformer, Flow Circulation.